2017
DOI: 10.1071/an15134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of oriental herbal medicine residue and methyl sulfonyl methane on the growth performance and meat quality of ducks

Abstract: The present study was conducted to determine the effect of supplementation with oriental herbal medicine residue (OHMR) and methyl sulfonyl methane (MSM) on the growth performance and meat quality of ducks during a 42-day feeding period. In total, 270 Cherry Valley male ducklings were fed diets supplemented with 0.03% MSM alone (MSM group) and with a combination of 0.03% MSM and 0.5% OHMR (MSM–OHMR group). Supplementing the diet with a combination of OHMR and MSM resulted in a significant (P < 0.05) decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 47 publications
5
13
3
3
Order By: Relevance
“…This study showed that the inclusion of MSM (0.3%) improved final BW and BWG during the periods of days 22–42 and days 1–42 as well as reduced F/G during the period of days 22–42 in Pekin ducks. On the contrary, Hwang et al. (2017) reported no effect of MSM (0.03%) on BWG, FI, or F/G in Cherry Valley male ducks.…”
Section: Discussionmentioning
confidence: 88%
“…This study showed that the inclusion of MSM (0.3%) improved final BW and BWG during the periods of days 22–42 and days 1–42 as well as reduced F/G during the period of days 22–42 in Pekin ducks. On the contrary, Hwang et al. (2017) reported no effect of MSM (0.03%) on BWG, FI, or F/G in Cherry Valley male ducks.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies in pigs and prawns have also showed that CHMs supplements in diet significantly enhanced growth performance of pigs and prawns under high temperature stress (Windisch et al, 2008;Liu et al, 2010;Song et al, 2010;Dong et al, 2012). However, some inconsistent observations were reported, suggesting dietary CHMs supplements had no effect on animal performance (Botsoglou et al, 2002;Hwang et al, 2017). These different responses to CHMs in different studies might be due to herbal species and their complexity of bioactive components in herbs.…”
Section: Discussionmentioning
confidence: 98%
“…위 및 근육의 합성에 이용된다 (Matin et al, 2013). 그러므로 육계에 0.2%의 식이유황을 급여하면 성장이 높아지며, 폐사 율이 감소되었다고 하였으며 (Shin et al, 2013), 오리에서는 유기황 0.03%의 급여로 고기에서 보수력과 불포화지방산 함량이 증대되었다고 하였다 (Hwang et al, 2017). 또한 산란 계 사료에 식이유황 0.1% 수준으로 급여시 계란의 점도, 난 백높이 및 저장기간이 향상되었으며, 난각강도와 두께를 개 선하였다 (Park et al, 2010).…”
unclassified
“…0.4% 급여구에서 0.2975%로 제일 높게 나타났다. 이전 연구 에서 화산이나 석유 포함되어 있는 무기황의 급여는 독성이 있고 흡수율이 낮으므로 섭취시 대부분이 배설된다고 하였 지만 (Hwang et al, 2010), 육용 오리에서 유기황의 급여시 가슴육에서 황 함량이 증가되었다 (Hwang et al, 2017). 또한 Utterback et al(2005) (Shedlock and Shen, 2003), 이와 관련하여 IL-2는 CD4+의 증식과 생산에 관여하는 면역 사이토카인으로 보고되었다 (Janeway et al, 1999 Fig.…”
unclassified